3D numerical calculations of tangent leakages in scroll compressor during unsteady process. (2017) - Rak, Józef; Pietrowicz, S?awomir; Gnutek, Zbigniew
A continuous increase in computing power brought progress in a scroll compressor modelling. The early simplified models now can be supplemented with a significantly more detailed CFD models. These models require a high resolution meshes due to the characteristics of the positive displacement machines. The working chambers geometries are evolving in time due to the vanes movement. For that reason, a moving boundary conditions have to be applied to the numerical model. This entails it is necessary to use a mesh deformation and to modify the solved equations so they are correct in the changing reference system. In order to remain a high mesh quality, a procedure for remeshing also has to be introduced. In return, the solution gives a better insight into the process compared to the simplified models. In the paper, a numerical spatial scroll compressor model with a mesh generation procedure is presented. The calculations were performed for different values of the radial clearances between scroll wraps. The clearance causes a leakage between higher and lower pressure chambers and affects their mass and energy balance. A comparison between the numerical and an analytical solution was used as a benchmark for the results.